Análise do setor bancário: a presença dos bancos espanhóis no Brasil - Bezerra, Ricardo Ramos (2005)
Presents the reasons that lead Spanish banks to invest in the Brazilian banking sector and analyses the results of that strategy. Discuss the relationship among the global consolidation process in the banking sector, the strategies used by Spanish banks and the effects in the Brazilian banking system. Describes the Brazilian banking sector formation and its consolidation after the Real Plan. Analyses the internationalization of Spanish banks and the Latin America option. Discuss the expectations with the presence of foreign banks, the competition in Brazilian banking sector, and the Spanish banks results.